Box–Behnken design for the optimization of the removal of Cr(VI) in soil leachate using nZVI/Ni bimetallic particles. Issue 8 (17th November 2018) - He, Siying; Zhu, Fang; Li, Luwei; Ren, Wentao
Abstract: Soil leachate containing Cr(VI) was remediated in this investigation using nano zero valent iron/nickel bimetallic particles (nZVI/Ni) prepared by borohydride reduction method. To validate and optimize interactions among different parameters (reaction time, temperature, and the initial pH value) for the reduction of Cr(VI) in soil leachate, the Box–Behnken design (BBD) model of response surface methodology was employed. Seventeen experiments were carried out with three center points. F - and P -values obtained from this model suggested that the BBD model was suitable for analyzing the interaction among different parameters. Correlation coefficients of 0.9865 and 0.9692 were obtained for R 2 and adjusted R 2, respectively. Results showed that the interaction between initial pH value and temperature had an significant effect on the removal rate of Cr(VI) in soil leachate by nZVI/Ni. The optimum condition was when pH was 5, temperature was 313 K, and reaction time was 20 min, the removal rate could reach 99.36%. This study provided a reference for the further research and practical application of nZVI/Ni to remediate Cr(VI) from soil leachate.